Implementation of Lumbung Mataraman to Support Family Food Resilience in Kulon Progo Regency - Kuning Retno Dewandini Sri; Religia Yoga; Fauzan Farid Al Hamdi Muhammad; Devita Sari Sandra (SHS Web of Conferences)
This research aims to evaluate the implementation of the Lumbung Mataraman program, an initiative by the Daerah Istimewa Yogyakarta government, in enhancing family food resilience in Kulon Progo Regency. Targeted at women farmer groups, the program encourages the use of yard land for cultivating various horticultural crops and livestock as part of community empowerment. A qualitative approach was employed to analyze the program’s processes, including planning, implementation, monitoring, and evaluation. The study highlights that the program’s success is influenced by key aspects such as the interests of involved actors, benefits, decision-making roles, and available resources. Additionally, the contextual factors, such as power dynamics, institutional characteristics, and stakeholder compliance, significantly contribute to the program’s effectiveness. The results reveal that Lumbung Mataraman successfully supports food resilience by empowering women farmers to utilize their yards for cultivation, thereby improving their ability to meet family food consumption needs. However, there is a need to further examine the long- term sustainability and scalability of the program. The study’s findings suggest that replicating similar community-based empowerment programs could improve food security in rural areas. Future policies should focus on enhancing support for such initiatives to foster greater agricultural productivity and food resilience in the region.